Standing in truck, second from the right: Augustin Souchy; behind bars: Karl Potsler and Otto Hartwig. Campaign for the release of Sacco and Vanzetti
Standing in truck, second from the right: Augustin Souchy; behind bars: Karl Potsler and Otto Hartwig. Campaign for the release of Sacco and Vanzetti.